Reflexions on Agro-pastoralists in the WANA region: challenges and future priorities - Ates, S.; Louhaichi, Mounir (2012)
Rangeland resources are among the most important – and almost certainly the most neglected – agro ecosystem component in dry areas. They are the largest land-use category, home to the poorest segment of the population, and crucial for millions of small-scale livestock producers. The availability of grazing resources for livestock in the world’s drylands is low and erratic due to the recurrent droughts in which animals can often fall victim. The insufficient feed supply has been in decline with widespread degradation of rangelands arising from overgrazing, loss of biodiversity, and human induced global warming. Moreover, the feed gap today is more pronounced as the livestock population has increased substantially as a result of growing demand for animal products in West Asia and North Africa (WANA) region. An important option to compensate the shortage of feed from rangelands is to grow more forage without compromising food security. It is evident that the livestock keepers in the drylands of WANA region can only attain the goal of desirable animal production if the rangelands are adequately managed. However, protection and rehabilitation of degraded rangelands depend upon complicated factors such as land tenure, control of grazing, intensified forage production, and recurrent droughts.